Curcumol simultaneously induces both apoptosis and autophagy in human nasopharyngeal carcinoma cells. (8th November 2021) - Wang, Juan; Liu, Guoxiang; Li, Xiaojuan; Huangfu, Mengjie; Liu, Yisa; Li, Xumei; Yu, Dan; Zhou, Luwei; Chen, Xu
Abstract: Autophagy is usually considered as a protective mechanism against cell death, and in the meantime, leads to cell injury even apoptosis. Apoptosis and autophagy are very closely connected and may cooperate, coexist, or antagonize each other on progressive occurrence of cell death triggered by natural compounds. Therefore, the interplay between the two modes of death is essential for the overall fate of cancer cells. Our previous study revealed that curcumol induced apoptosis in nasopharyngeal carcinoma (NPC) cells. Recently, curcumol was found to induce autophagy in cancer cells. However, whether curcumol can induce NPC cells autophagy and the effects of autophagy on apoptosis remain elusive. In this study, we found that curcumol induced autophagy through AMPK/mTOR pathway in CNE‐2 cells. Moreover, inhibiting autophagy by autophagy inhibitor 3‐methyladenine (3‐MA) or apoptosis inhibitor z‐VAD‐fmk significantly increased proliferation while attenuated apoptosis and autophagy compared with the curcumol 212 μM group. In contrast, combining curcumol with autophagy agonist rapamycin and apoptosis inducer MG132 synergized the apoptotic and autophagic effect of curcumol. Taken together, our study demonstrates that curcumol promotes autophagy in NPC via AMPK/mTOR pathway, induces autophagy enhances the activity of curcumol in NPC cells; the combination of autophagy inducer and curcumol can be a new therapeutic strategy for NPC.